Interleukin 31 in insect bite hypersensitivity—Alleviating clinical symptoms by active vaccination against itch. Issue 4 (6th February 2020) - Olomski, Florian; Fettelschoss, Victoria; Jonsdottir, Sigridur; Birkmann, Katharina; Thoms, Franziska; Marti, Eliane; Bachmann, Martin F.; Kündig, Thomas M.; Fettelschoss‐Gabriel, Antonia
Abstract: Background: Insect bite hypersensitivity (IBH) is the most common seasonal pruritic allergic dermatitis of horses occurring upon insect bites. In recent years, a major role for IL‐31 in allergic pruritus of humans, monkeys, dogs, and mice was acknowledged. Here, we investigate the role of IL‐31 in IBH of horses and developed a therapeutic vaccine against equine IL‐31 (eIL‐31). Methods: IL‐31 levels were quantified in allergen‐stimulated peripheral blood mononuclear cells (PBMCs) and skin punch biopsies of IBH lesions and healthy skin from IBH‐affected and healthy horses. The vaccine consisted of eIL‐31 covalently coupled to a virus‐like particle (VLP) derived from cucumber mosaic virus containing a tetanus toxoid universal T‐cell epitope (CuMVTT). Eighteen IBH‐affected horses were recruited and immunized with 300 μg of eIL‐31‐CuMVTT vaccine or placebo and IBH severity score was recorded. Results: IL‐31 was increased in PBMCs and exclusively detectable in skin lesions of IBH‐affected horses. Vaccination against eIL‐31 reduced delta clinical scores when compared to previous untreated IBH season of the same horses and to placebo‐treated horses in the same year. The vaccine was well tolerated without safety concerns throughout the study. Conclusion: TH2‐derived IL‐31 is involved in IBH pathology and accordingly the immunotherapeutic vaccination approach targeting IL‐31 alleviated clinical scores in affected horses. Abstract : Equine IL‐31 is detectable in insect bite hypersensitivity (IBH) skin lesions upon insect bites and mediates pruritus by targeting peripheral nerves. IL‐31 is absent in skin biopsies from nonlesional or healthy skin. eIL‐31‐CuMVTT vaccine successfully induces autoantibodies against IL‐31 and reduces lesion scores in horses.